KAJIAN RENCANA TATA RUANG WILAYAH BERDASARKAN RISIKO BENCANA GEMPA BUMI DI KOTA JAYAPURA - Yabansabra, Werenfrida; Rante, Harmonis; Awaluddin Kurniatullah, Duha (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
A study has been conducted on the typology of earthquake disaster-prone areas in the city of Jayapura and the suitability of Regional Spatial Planning (RTRW) for land use capacity in the city of Jayapura. The study onearthquake disaster-prone area typology aims to determine the distribution of stability levels of the area againstthe risk of earthquakes. This study employs a weighting matrix method for area stability based on the Minister ofPublic Works Regulation No. 21 of 2007 concerning Guidelines for Spatial Planning of Volcanic Eruption andEarthquake-Prone Areas (Department of Public Works, 2007). The research results indicate that the final score forthe city of Jayapura is between 30 - 45, which falls into all stability categories: stable and less stable. Thepercentage of area for each category is 97.81% for Stable Type A, 1.91% for Stable Type B, and 0.28% for LessStable Type C. The typology of earthquake disaster-prone areas in Jayapura based on stability scores falls intocategories A, B, and C. The study on the suitability of the Regional Spatial Planning (RTRW) for 2013-2033 with the land usecapacity in Jayapura was assessed by scoring data on land capacity and land use, followed by an overlay analysis.This resulted in a land capacity suitable for development of 57,039.39 hectares, or about 60.48% of the study area,while approximately 37,272.96 hectares, or around 39.52%, were deemed unsuitable.